2020
DOI: 10.1038/s41598-020-63045-0
|View full text |Cite
|
Sign up to set email alerts
|

Looking to recognise: the pre-eminence of semantic over sensorimotor processing in human tool use

Abstract: Alongside language and bipedal locomotion, tool use is a characterizing activity of human beings. Current theories in the field embrace two contrasting approaches: "manipulation-based" theories, which are anchored in the embodied-cognition view, explain tool use as deriving from past sensorimotor experiences, whereas "reasoning-based" theories suggest that people reason about object properties to solve everyday-life problems. Here, we present results from two eye-tracking experiments in which we manipulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 78 publications
2
18
1
Order By: Relevance
“…Interestingly, these results above seem to contradict prior studies; two research found that participants gazed more at the grasping part when they could freely observe a familiar tool and an object with a consistent combination ( Federico and Brandimonte, 2019 , 2020 ). However, in one of these studies, when the combination was consistent and presented at a spatially distant location, participants gazed more at the functional part of the tool ( Federico and Brandimonte, 2019 ), namely, if the tool and the combined object are not in a spatial position where they can be manipulated, people may not automatically imagine the action of using the tool.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…Interestingly, these results above seem to contradict prior studies; two research found that participants gazed more at the grasping part when they could freely observe a familiar tool and an object with a consistent combination ( Federico and Brandimonte, 2019 , 2020 ). However, in one of these studies, when the combination was consistent and presented at a spatially distant location, participants gazed more at the functional part of the tool ( Federico and Brandimonte, 2019 ), namely, if the tool and the combined object are not in a spatial position where they can be manipulated, people may not automatically imagine the action of using the tool.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, in our study, we did not present another object in combination with the tool; instead, we presented only the tool. This experimental condition corresponds methodologically to the free viewing condition of Federico and Brandimonte (2020) , in which the object and the tool are inconsistently combined. Moreover, the short-term recognition task of tools (or objects) present in Federico and Brandimonte (2020)’ s study corresponds methodologically to the use condition in the current study, since it involves the process of recalling how to use the tools (or objects).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations